Application of Petrochemical Wastewater Treatment Processes - Muhaba, Sitra; Mulubrhan, Freselam; Mohd Ridzuan, Darun (AIP Publishing, 2022)
Due to the fact that petroleum products purification is a long process and the complexity of the production equipment used for petroleum production, there will be a huge amount of petrochemical wastewater production, which contains residual oil and other harmful substances. The release of the petrochemical wastewater directly to the surrounding will cause serious damage to the air, land, water and living organisms. There are numerous processes used to treat the wastewater from the petrochemical plants, however, there is a limitation of literature that studies all the treatment stages. Most of the studies only focus on one or two wastewater treatment processes, overlooking the tertiary (advanced) treatment stage. The objective of this paper is to analyze all the stages of petrochemical wastewater treatment and its effect on the environment. The study investigates more than 36 papers dealing with wastewater treatment processes. The finding shows that the primary treatment techniques (physical (Mechanical) and physio-chemical treatment) can remove up to 80% (average) of the oil from the wastewater. American petroleum institute (API) separator, Corrugated plate interceptor (CPI) separator and Parallel plate interceptor (PPI) separator are used for physical treatment technologies. On the other hand, the secondary (biological) treatment process can remove approximately 75% (average) of the chemical oxygen demand (COD) from the wastewater. The tertiary (chlorination, final sedimentation, filtration) treatment process also termed the polishing stage. It can remove up to 90% (average) of COD from the wastewater. gravity sand-filtration, membrane-based filtration such as microfiltration and ultrafiltration membranes are some tertiary treatment processes.